A Rare Case of Acute-Onset Spastic Quadriparesis Caused by a Chondroma of the Cervical Spine. (23rd May 2019) - Momota, Kaori; Nishisho, Toshihiko; Miyagi, Ryo; Toki, Shunichi; Yamashita, Kazuta; Tezuka, Fumitake; Takata, Yoichiro; Sakai, Toshinori; Nagamachi, Akihiro; Maeda, Toru; Sairyo, Koichi
Abstract : Chondromas are benign cartilaginous tumors that occur very rarely in the spine. Moreover, chondromas of the extraskeletal origin are also very rare. In this case report, we describe an extremely rare case of chondroma arising from the ligamentum flavum in the cervical spine. A 67-year-old man presented to our clinic with acute-onset spastic quadriparesis. We performed emergent magnetic resonance imaging and found an epidural mass in the right ligamentum flavum at C4-C5. The acute-onset presentation was suspicious for intraligamentous hematoma in the ligamentum flavum at this level. We performed emergency decompression surgery and en bloc removal of the epidural mass with the right C4 and C5 lamina. The lesion had the appearance of cartilaginous tissue rather than hematoma. Based on the histological investigation, the final diagnosis was intraligamentous chondroma of the cervical spine. The quadriparesis improved postoperatively, as did the results of manual muscle testing in the affected area, and he was able to resume walking independently with a cane. At the one-year follow-up, the manual muscle testing results were almost normal. Surgeons should keep in mind the possibility of benign tumors including chondroma of the cervical spine when a patient presents with acute-onset quadriparesis.